Has Globalization Increased Inequality? - Dreher, A.; Gaston, Noel (Wiley-Blackwell Publishing Ltd., 2008)
There is no shortage of theories that purport to explain why globalization may have adverse, insignificant, or even beneficial effects on income and earnings inequality. Surprisingly, the empirical realities remain an almost complete mystery. In this paper, we use data on industrial wage inequality, household income inequality as well as measures of the economic, social and political dimensions of globalization to examine this controversial issue. Overall, while we find that globalization has exacerbated inequality; this is particularly true in the case of income inequality in OECD countries.